Using the Saphenous Artery and Great Saphenous Vein Combined with Anterolateral Thigh Flap to Treat Skin Defects after Amputation - Kong, Ling Dong; Cheng, Han Xiong; Nie, Tao; Dai, Min (Journal of Reconstructive Microsurgery Open, 2018)
Background Aim of this study was to determine the feasibility of using the saphenous artery (SA) and great saphenous vein (GSV) as recipient vessels, combined with anterolateral thigh (ALT) flap, in the treatment of skin defects after lower limb amputation.Methods From June 2015 to June 2017, 12 patients (average age, 33.5 years; range, 14–56 years; males, 9; female, 3) with large skin defects and symptoms of bone exposure in the proximal lower extremity were included in our study. The patients underwent emergency treatment and multiple debridement combined with vacuum sealing drainage therapy, followed by free flap surgery using the SA and GSV as recipient vessels, and ALT to cover the wound.Results All 12 patients who underwent free flap surgery survived, but two patients had distal flap necrosis, which, however, was salvaged with conservative measures. All patients were satisfied with the postoperative outcome at the 3 and 6-month follow-up.Conclusion The SA and GSV can be used as recipient vessels, combined with ALT, to treat skin defects after lower limb amputation.
Keywords: saphenous artery; great saphenous vein; anterolateral thigh flap; amputation